Oncolytic adenovirus-mediated expression of CCL5 and IL12 facilitates CA9-targeting CAR-T therapy against renal cell carcinoma - Lin Fang; Weiping Tian; Chen Zhang; Xueyan Wang; Wanjing Li; Qi Zhang; Yuxin Zhang; Junnian Zheng (Elsevier, 2023)
Chimeric antigen receptor T-cell (CAR-T) is particularly prominent in hematological but not in solid tumors, mainly based on the complex tumor immune microenvironment. Oncolytic virus (OVs) is an emerging adjuvant therapy method. OVs may prime tumor lesions to induce anti-tumor immune response, thereby enhancing CAR-T cells functionality and possibly increasing response rates. Here, we combined CAR-T cells targeting carbonic anhydrase 9 (CA9) and an oncolytic adenovirus (OAV) carrying chemokine (C-C motif) ligand 5 (CCL5), cytokine interleukin-12 (IL12) to explore the anti-tumor effects of this combination strategy. The data showed that Ad5-ZD55-hCCL5-hIL12 could infect and replicate in renal cancer cell lines and induced a moderate inhibition of xenografted tumor in nude mice. IL12 mediated by Ad5-ZD55-hCCL5-hIL12 promoted the phosphorylation of Stat4 in CAR-T cells, induced CAR-T cells to secrete more IFN-γ. We also found that Ad5-ZD55-hCCL5-hIL-12 combined with CA9-CAR-T cells significantly increased the infiltration of CAR-T cells in tumor mass, prolonged the survival of the mice and restrained tumor growth in immunodeficient mice. Ad5-ZD55-mCCL5-mIL-12 could also increase CD45+CD3+T cell infiltration and prolong mice survival in immunocompetent mice. These results provided feasibility for the combination of oncolytic adenovirus and CAR-T cells, which demonstrated the sufficient potential and prospects of CAR-T for the treatment of solid tumors.